Impact of Social Media Marketing on Buying Behaviors of Superstore Customers in Bangladesh (PYC Nepal Journal of Management, 2021)
This study aims at identifying the impact factors of social media marketing on the buying behaviors’ of superstore customers in Bangladesh. Altogether, 291 buyers were surveyed from five superstores of Bangladesh such as, Agora, Meena Bazar, Shwapno, Almas Super Shop, and Nandan. A structured questionnaire with five points Likert scale was used to survey the customers. Descriptive statistics were used to present the profiles of the respondent customers while inferential statistics like Factor Analysis was used to identify the impact factors and Multiple Regression Analysis was used o identify the relationships between the impact factors and the overall impact on purchase decision of the customers. Study identified four significant impact factors such as, quick searching and verification of authenticity of product information, easy to order and saving time, customers addiction to media buying, and awareness of innovative and new products that induce the superstore customers to make their purchase decisions. This study suggests that the policymakers should focus on authenticity of product information, easy to order system that saves time, publicity of innovative and variety of products, and customer addicted towards media marketing for making the customers inclined towards buying the products and services from superstores of Bangladesh.